2021
DOI: 10.18087/cardio.2021.11.n1801
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of trimetazidine – an inhibitor of free fatty acids oxidation in the treatment of patients with stable angina pectoris and heart failure

Abstract: Aim      To evaluate efficacy of modified-release trimetazidine (TMZ) included into the standard therapy for patients with stable angina and chronic heart failure (CHF) as a part of a subgroup analysis in the PERSPECTIVE study.Material and methods  The study included 806 patients: group 1 (n=691), patients receiving a standard therapy and modified-release TMZ (TMZ group); and group 2 (n=115), patients receiving a standard therapy (control group). Total duration of the study was 12 months.Results In the TMZ gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Six studies (21%) were conducted in Russia and not reported in English. [23][24][25][26][27][28] Only two studies were conducted after the latest major revision of the European Society of Cardiology (ESC) HF guidelines in 2021, which explains the limited HF-background therapy (table 1, online supplemental table A3).…”
Section: Search Resultsmentioning
confidence: 99%
“…Six studies (21%) were conducted in Russia and not reported in English. [23][24][25][26][27][28] Only two studies were conducted after the latest major revision of the European Society of Cardiology (ESC) HF guidelines in 2021, which explains the limited HF-background therapy (table 1, online supplemental table A3).…”
Section: Search Resultsmentioning
confidence: 99%
“…In an RCT study, no nonsustained ventricular tachycardia was observed in the mavacamten treatment group, but no data about the incidence of TdP was reported ( 35 ). Trimetazidine has been shown to shorten QT intervals in research ( 36 ). As a result, TdP is unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Trimetazidine ( Figure 1 ), traditionally used in the management of angina pectoris [ 7 ], is renowned for its efficacy as an anti-ischemic agent [ 8 ]. Recently, it has garnered attention for its potential therapeutic use beyond its primary indication.…”
Section: Introductionmentioning
confidence: 99%